2019
DOI: 10.3390/cells8121475
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial MiRNA in Cardiovascular Function and Disease

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs functioning as crucial post-transcriptional regulators of gene expression involved in cardiovascular development and health. Recently, mitochondrial miRNAs (mitomiRs) have been shown to modulate the translational activity of the mitochondrial genome and regulating mitochondrial protein expression and function. Although mitochondria have been verified to be essential for the development and as a therapeutic target for cardiovascular diseases, we are just beginning to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 108 publications
1
48
0
Order By: Relevance
“…It is plausible that muted expression of Complex I—and therefore lower ROS production—permits SARS-CoV-2 propagation. Additional reports on respiratory viruses such as RSV have indicated that Complex I inhibition could promote efficient viral replication 27 . SARS-CoV-2 not only decreased expression to many NDUF family of genes, but also several mitochondrial ribosome protein related genes in primary cells and BALF, observations of which, however, did not carry over to cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that muted expression of Complex I—and therefore lower ROS production—permits SARS-CoV-2 propagation. Additional reports on respiratory viruses such as RSV have indicated that Complex I inhibition could promote efficient viral replication 27 . SARS-CoV-2 not only decreased expression to many NDUF family of genes, but also several mitochondrial ribosome protein related genes in primary cells and BALF, observations of which, however, did not carry over to cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these miRs are known to act on mitochondria and regulate mitochondrial biogenesis, dynamics, and mitophagy (Amakiri et al., 2019). Recent studies on mitochondrial miRs have revealed insights into their importance in regulating mitochondrial dynamics under different pathological conditions (Dewanjee & Bhattacharjee, 2018; John et al., 2020; Reddy, Manczak, et al., 2017; Song et al., 2019). Barrey and co‐workers (2011) identified 169 miRs in mitochondria, which are thought to regulate polypeptide genes in the mitochondrial genome, energy production, and oxidative phosphorylation.…”
Section: Failure Of the Ubiquitin–proteasome System In Neurodegeneratmentioning
confidence: 99%
“…MicroRNA, a Direct Attack on the Viral Genome The miRNAs are small, non-coding, single-stranded RNA molecules, which are known to modulate a variety of vital physiological processes including RNA silencing, post-transcriptional regulators of gene expression involved in cardiovascular development and health [70][71][72][73][74][75]. Several thousand human genes, amounting to about one third of the whole genome, are potential targets for regulation by the several hundred miRNAs encoded in the genome [76].…”
Section: Current Therapeutic Strategies For the Development Of An Effmentioning
confidence: 99%